2017
DOI: 10.3904/kjim.2015.185
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of endoscopic ultrasonography non-traversability in patients with locoregional esophageal cancer receiving multimodality therapy

Abstract: Background/AimsApproximately 30% of esophageal cancer (EC) patients cannot complete endoscopic ultrasonography (EUS) due to malignant stricture (EUS non-traversability). This study examines clinical implications of EUS non-traversability in patients with advanced locoregional squamous EC receiving preoperative chemoradiotherapy (CRT) followed by esophagectomy.MethodsWe retrieved data on 89 consecutive patients with advanced locoregional squamous EC (stage II or III). Relevant clinical and tumor-specific parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…EUS has been widely applied in daily practice for evaluating the extent of local tumor infiltration and local lymph node status of esophageal cancer with excellent accuracy before treatment (17). However, it is reported that due to esophageal stenosis, EUS could not be performed successfully in about 30% of esophageal cancer patients before treatment (5,6). So far, only a small number of studies have been carried out evaluating the impact of endoscopic finding of cancerous esophageal stenosis before treatment on the survival of esophageal cancer patients but drawn controversial conclusions because of the limited sample size (5-9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…EUS has been widely applied in daily practice for evaluating the extent of local tumor infiltration and local lymph node status of esophageal cancer with excellent accuracy before treatment (17). However, it is reported that due to esophageal stenosis, EUS could not be performed successfully in about 30% of esophageal cancer patients before treatment (5,6). So far, only a small number of studies have been carried out evaluating the impact of endoscopic finding of cancerous esophageal stenosis before treatment on the survival of esophageal cancer patients but drawn controversial conclusions because of the limited sample size (5-9).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, taken together, we believe that endoscopic finding of cancerous esophageal stenosis before treatment was significantly correlated to poor prognosis of esophageal cancer patients. The reasons why cancerous esophageal stenosis had unfavorable impact on prognosis of esophageal cancer patients may be explained by the facts that esophageal stenosis was associated with higher tumor stage, larger tumor burden and poorer tumor differentiation as well as poor nutrition status (6,7,16). Therefore, for patients with cancerous esophageal stenosis, neoadjuvant therapy may be more emphasized before surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the major negative prognostic factors reported in patients receiving preoperative CRT and esophagectomy due to locally advanced esophageal squamous cell carcinoma is endoscopic ultrasonography (EUS) non-traversability. [ 8 ] However, only limited studies have investigated the impact that conventional endoscopic traversability has on the prognosis in patients with locally advanced squamous cell carcinoma that have been treated with definitive CRT. Because esophagogastroduodenoscopy with biopsy plays an essential role in histologically confirming esophageal cancer, we questioned whether the prognosis of patients with esophageal squamous cell carcinoma can be easily predicted according to endoscopic traversability.…”
Section: Introductionmentioning
confidence: 99%